Library Structure of Dynamic Simulation for Combined Heat and Power Plant in Modelica Language - Amir, Abdul Razak (Trans Tech Publications, 2012)
The most common form of energy recycling system is Combined Heat and Power (CHP) plants. The CHP plant is a complex system and still under intensive development by many researchers. The system needs to be developed in quick and efficient manners with low resources based on modeling and simulation method. With the development of CHP library in open source Modelica language, it could be used as a base for further advancement of CHP technology. The aim of this work is to design a structure of initial version of a model library for the dynamic simulation of Combined Heat and Power plants (CHP). Modular approach and top-down design have been implemented in the model library development. A solid base for this work is defined which includes rules in modeling the components (e.g. robustness and reusability), default library structure arrangement and model documentation. By strictly follow thr rules and concepts introduced in this work, the mistakes in modeling is minimized. The designed library in Modelica language will provide an organized environment in modeling a CHP plant.